If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -6) + x = 16 Reorder the terms: 2(-6 + 3x) + x = 16 (-6 * 2 + 3x * 2) + x = 16 (-12 + 6x) + x = 16 Combine like terms: 6x + x = 7x -12 + 7x = 16 Solving -12 + 7x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 7x = 16 + 12 Combine like terms: -12 + 12 = 0 0 + 7x = 16 + 12 7x = 16 + 12 Combine like terms: 16 + 12 = 28 7x = 28 Divide each side by '7'. x = 4 Simplifying x = 4
| 8x^2-31x-45=0 | | 124-w=229 | | 5x-4x+3=-33 | | 3(2a-5)+4= | | 5(5x^2-8x-4)=0 | | 5ln(x)=1 | | 3x-8=16-9x | | 7=-t/4-9 | | 3qt=pt | | 3(2a-5)+4(3a-2)= | | k/3-23=-36 | | x^2+9x^2=25 | | -4(-5u+6)-7u=5(u-5)-5 | | 2+4w=-14 | | 6=d/15+2 | | x+3x-70=180 | | 41=2x+15 | | -3x+9=6x-99 | | 2(u-8)-8u=-28 | | 50+5x=3x-40 | | 20x=380 | | 18x+7=400+5x | | 4x+3/4=-10 | | 4w+2w=18 | | 7-4(2t-7)=-21 | | 2y+8=180 | | 2(3v+8)=70 | | 17y+2x=-29 | | 7x+8-9x=14-15x+13x-6 | | -5(-6w+2)-6w=6(w-2)-8 | | 2=3x+14 | | (12g^1)= |